Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/ofid/ofz306
|View full text |Cite
|
Sign up to set email alerts
|

High Hepatitis E virus (HEV) Positivity Among Domestic Pigs and Risk of HEV Infection of Individuals Occupationally Exposed to Pigs and Pork Meat in Hanoi, Vietnam

Abstract: Background Hepatitis E virus (HEV) infection can occur through consumption of undercooked pork meat or exposure to animal feces. Because there are scarce data only in developing countries, we assessed whether pigs might be a potential source of human HEV infections in Vietnam. In addition, we determined anti-HEV seroprevalences in the general population and in individuals professionally exposed to pigs and pork meat. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 41 publications
1
25
1
1
Order By: Relevance
“…Further epidemiological study needs to be conducted to establish a transmission link between pigs and humans in Son La province. Also, one recent study showed that the HEV seroprevalence was higher among individuals occupationally exposed to pig and pork products [21]. Therefore, the human health impact of HEV should be properly defined to establish appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further epidemiological study needs to be conducted to establish a transmission link between pigs and humans in Son La province. Also, one recent study showed that the HEV seroprevalence was higher among individuals occupationally exposed to pig and pork products [21]. Therefore, the human health impact of HEV should be properly defined to establish appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that HEV is circulating in pigs (prevalence: 19.1% in fecal samples and 8.2% in rectal samples) while humans showed 31.7% seroprevalence [20]. In addition, a recent study in Vietnam found that pig farmers, slaughterhouse workers and pork meat retailers had high seroprevalence compared to unexposed groups [21]. Also, it showed that HEV was detected from liver tissues in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Further epidemiological study needs to be conducted to establish a transmission link between pigs and humans in Son La province. Also, one recent study showed that the HEV seroprevalence was higher among individuals occupationally exposed to pig and pork products [21]. Therefore, the human health impact of HEV should be properly de ned to establish appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Further epidemiological study needs to be conducted to establish a transmission link between pigs and humans in Son La province. Also, one recent study showed that the HEV seroprevalence was higher among individuals occupationally exposed to pig and port meat [25]. Therefore, the human health impact of HEV should be properly de ned to establish appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that HEV is circulating in pigs (prevalence: 19.1% in fecal samples and 8.2% in rectal samples) while humans showed 31.7% seroprevalence [24]. In addition, a recent study found that pig farmers, slaughterhouse workers and pork meat retailers had high seroprevalence compared to unexposed groups [25].…”
Section: Introductionmentioning
confidence: 99%